PERANCANGAN SISTEM INFORMASI AKUNTANSI PENERIMAAN KAS DAN PENGELUARAN KAS DI CV. AZKHA MULYA JAYA - Samekto, Deby; Nugroho, Mulyanto; Arifin, Mochammad (LPPM Universitas Bina Bangsa, 2025)
The purpose of this research is to design an Accounting Information System (AIS) to manage cash receipts and disbursements at CV Azkha Mulya Jaya. This company struggles with cash management due to a manual system based on Microsoft Excel, which is prone to errors and delays in reporting. The implementation of this system is expected to enhance efficiency and accuracy in managing the company's cash flow. This research employs a qualitative descriptive approach using the System Development Life Cycle (SDLC), which includes planning, analysis, design, and evaluation stages. Data were collected through interviews with finance staff, direct observations of operational processes, and analysis of supporting documents such as invoices, receipts, and financial reports. The findings indicate that the developed information system can automate the recording of cash receipts and disbursements, as well as the automatic generation of financial reports. The system features a user-friendly interface and capabilities for generating daily and monthly cash flow reports more quickly and accurately. Ultimately, this system aims to enable the company to monitor cash flow more efficiently, reduce human error, and improve financial transparency and accountability. This research highlights the importance of integrating technology into financial management for better operational performance.